Exploring Working Capital Management Strategies and Challenges in Small and Medium Construction Enterprises in Douala, Cameroon - Nyume Nyingmeh, Blaise (Technium Social Sciences Journal, 2026)
The working capital management (WCM) strategies often transform according to changing preferences in terms of cash flow management, cost mitigation, and other strategies to stabilize their financial performance. Construction companies need efficient WCM strategies to achieve their financial goals by managing their current assets and liabilities. Very few studies have investigated the WCM strategies used by the construction companies in Cameroon. Therefore, this study focuses on construction companies from Cameroon, which are categorized as SMEs. Study has employed a qualitative approach to fulfil objectives. Data collected by conducting semi-structured interviews with 22 employees from two construction companies in Cameroon. NVivo has been used to conduct the analysis. Findings highlighted various WCM strategies, including effective management of inventory, cash, disputes, accounts payable, accounts receivable, and project costing. Identified challenges include political, economic, legal, environmental, social, and legal factors, which may influence the implementation of WCM strategies in construction firms in Cameroon.